Arduino-based embedded systems interfacing, simulation, and LabVIEW GUI - Singh, Rajesh; Gehlot, Anita; Singh, Bhupendra; Choudhury, Sushabhan (CRC Press, Taylor & Francis, 2018)
This book will help beginners to get started with Arduino-based embedded systems including essential know-how of the programming and interfacing of the devices. Book includes programming and simulation of Arduino-based projects and interfacing with LabVIEW, based on practical case studies. The book comprises of total twenty five chapters with description, working model of LabVIEW and programming with Arduino IDE.